Modelling of Three Phase System with Non-Newtonian Liquid Using Computational Fluid Dynamics Model - Abdulbari, Hayder A.; Kwaire, Asawer A.; Falih, Hussain M. (Knowledgia Review, Malaysia, 2009)
A 2 dimensional numerical simulation was used to describe the flow behaviour and circulation pattern of three phase system inside an isothermal slurry bubble column using a finite volume technique. The three phase system consists of; air as the gas phase, non-Newtonian solution of poly acryl amid (PAA) as the liquid phase, and alumina catalyst as the solid phase. To experimentally validate the code, local gas hold-up and bubble characteristics have been measured using a modified electrocondactivity probe. The model was based on the principle of continuity and momentum equations. The gas and liquid velocity were prescribed numerically and the gas velocity simulated agrees with experimental observation. The experimental results as well as the numerical results show that the gas velocity decreases with increasing the non-Newtonian behaviour of the system and this may due to the increasing in bubble coalescence.